KESIAPAN BELAJAR MANDIRI MAHASISWA UT DAN SISWA SMA UNTUK BELAJAR DENGAN SISTEM PENDIDIKAN TINGGI TERBUKA DAN JARAK JAUH DI INDONESIA - Samsul Islam (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2010)
The research aims to find out Self Directed Learning Readiness (SDLR) of potential students and prospective students (high school students) to learn by open and distance learning (ODL) in Indonesia. Research conducted by survey method. The population were high school students who are considered grade 12 as a potential candidate ODL student, a freshman, and ODL student at the Open University (UT). SDLR levels were measured by questionnaires Self-Directed Learning Readiness Scale (SDLRS) developed by Guglielmino (1989). The results showed that the SDLR level of high school students were statistically lower than the SDLR level of UT students, both new students and previous students. However, there were no statistically significant differences between the SDLR level of new students and previous students of UT. Score SDLRS obtained show that the UT student has average levels of SDLR. This means that UT students can successfully learn independently but they are not very responsible to determine learning needs, plan, implement, and evaluate their own learning. UT students who have the SDLR level above average are over 55 years students.